INFORMATION SYSTEMS DEVELOPMENT PLAN FOR DAVAO CENTRAL CONVENIENCE STORE CABALUNA - Krisseah Marie F. Hilay,; Jess Errol G. Awil,; Jofell R. Depena,; John Patrick P. Eleria,; Glendell C. Jadraque, (International Journal of Innovations in Engineering Research and Technology, 2021)
Discrepancies and inaccuracies are common problems in a manual system. It undermines the potential of the business to align with modernizing standards of the retail industry. Implementing an optimized information system reverses those errors into positive effects for the company. This paper conceptualized the issues which is the intent to resolve. Adapting to the Point-of-Sale system comprehends the business position and creates decisions out of the information. It automates major processes boosting productivity. Utilizing technology facilitates managing the volume of information. It offers security measures and flexibility in handling everyday transactions.